2021
DOI: 10.3390/microorganisms9081621
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Patterns of Rhoptry Kinases during the Eimeria tenella Life-Cycle

Abstract: Kinome from apicomplexan parasites is composed of eukaryotic protein kinases and Apicomplexa specific kinases, such as rhoptry kinases (ROPK). Ropk is a gene family that is known to play important roles in host–pathogen interaction in Toxoplasma gondii but is still poorly described in Eimeria tenella, the parasite responsible for avian coccidiosis worldwide. In the E. tenella genome, 28 ropk genes are predicted and could be classified as active (n = 7), inactive (incomplete catalytic triad, n = 12), and non-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Although rhoptry kinases are restricted to apicomplexans, phylogenetic analysis showed that most of the 28 rhoptry kinases from E. tenella ( 18 , 19 ) constitute a specific clade, organized into seven subfamilies ( 20 ), based on sequence homology and tandem repeat loci. Recently, we confirmed the dynamic transcription of 27 of these ropk genes during the parasite life cycle ( 21 , 22 ). No correlation could be found between subfamilies and stage transcription ( 21 ).…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Although rhoptry kinases are restricted to apicomplexans, phylogenetic analysis showed that most of the 28 rhoptry kinases from E. tenella ( 18 , 19 ) constitute a specific clade, organized into seven subfamilies ( 20 ), based on sequence homology and tandem repeat loci. Recently, we confirmed the dynamic transcription of 27 of these ropk genes during the parasite life cycle ( 21 , 22 ). No correlation could be found between subfamilies and stage transcription ( 21 ).…”
Section: Introductionmentioning
confidence: 52%
“…Recently, we confirmed the dynamic transcription of 27 of these ropk genes during the parasite life cycle ( 21 , 22 ). No correlation could be found between subfamilies and stage transcription ( 21 ). Three distinct transcription profiles were described: (i) with a constant and low expression across the parasite life cycle, (ii) with higher expression in the extracellular stages, and (iii) with higher expression in the intracellular stages.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Cells containing mature schizonts of Eimeria then rupture and release the merozoites ( 128 , 129 ). These merozoites of Eimeria undergo multiple cycles of schizogony, and then, due to unknown reasons, they mature into male and female gametes (micro- and macrogametes) ( 130 , 131 ). These gametes fuse to form zygotes that develop into unsporulated oocysts, which are then shed in the bird's feces ( 132 , 133 ).…”
Section: Methodsmentioning
confidence: 99%
“…TgROP16 is localized to the host cell nucleus after invasion ( Ong et al., 2010 ), phosphorylates signal transducer and activator of transcription STAT6 and STAT3 ( Yamamoto et al., 2009 ; Butcher et al., 2011 ) to bypass the protective immune-response of the host cell. In E. tenella , among 28 ROPKs differentially expressed during the life-cycle ( Ribeiro E Silva et al., 2021 ), only EtROP1 has been functionally characterised ( Diallo et al., 2019 ). It interacts with host p53, to inhibit host cell apoptosis and induce G0/G1 cell cycle arrest.…”
Section: Secreted/excreted Parasite Kinasesmentioning
confidence: 99%